Liver transplantation for alcoholic liver disease - Lucey, Michael R. (Nature reviews. Gastroenterology & hepatology, 2014)
Key Points Liver transplantation is the standard of care for patients with life-threatening alcoholic liver disease (ALD), but is controversial in patients with alcoholic hepatitis that is unresponsive to medical therapy Evaluation by an addiction specialist with an interest in transplant medicine is the best approach to assess prognosis for abstinence Patients with ALD undergoing liver transplantation have a similar survival benefit to recipients of a liver transplant who do not have ALD Alcohol relapse may lead to liver damage and increased mortality, albeit usually after many years of renewed drinking Patients with ALD have increased rates of mortality and morbidity attributable to cardiovascular disease and new-onset cancers of the aerodigestive tract after liver transplantation Cessation of smoking is an important goal in the care of patients with ALD after liver transplantation, as the increased mortality and morbidity is probably linked with smoking This Review outlines the nomenclature of addiction to alcohol and details how patients who drink to excess should be assessed for liver transplantation. Michael Lucey also explores the controversies about predicting future drinking behaviour and offering liver transplantation to patients with severe alcoholic hepatitis. Alcoholic liver disease (ALD) is the major cause of life-threatening liver disease in Western countries. Abstinence from alcohol is the foundation of all treatment programmes for patients with ALD. Liver transplantation is a valuable option for patients with life-threatening ALD. Although the role of liver transplantation in the treatment of alcoholic hepatitis that is unresponsive to medical therapy is controversial, the latest prospective studies support this approach. No single measure gives a reliable estimate of the risk of drinking relapses before or after liver transplantation, but careful evaluation by an addiction specialist with a particular interest in transplant medicine is the best available approach. Survival, both on the waiting list and after the operation, is better in patients with ALD than in patients with HCV infection. Alcohol relapse may lead to liver damage and increased mortality, albeit usually after many years of renewed drinking. After liver transplantation, patients with ALD have increased rates of mortality and morbidity that are attributable to cardiovascular disease and new-onset cancers of the aerodigestive tract. The latter are probably linked to the high prevalence of smoking in this population. Cessation of smoking is thus an important goal in the care of patients with ALD after they have undergone liver transplantation.